2017
DOI: 10.1007/s00256-017-2797-0
|View full text |Cite
|
Sign up to set email alerts
|

Giant angioleiomyoma of the sacral foramina: an unusual location

Abstract: Angioleiomyoma is a benign, vascular smooth muscle tumor originating from the tunica media of the vessel wall. In general, it typically arises in the cutaneous, subcutaneous tissue or fascia of the lower extremities in middle-aged women and is less than 2 cm in diameter. We report an unusual case of an angioleiomyoma of the sacral foramina in an 82-year-old man. MRI revealed a well-defined irregular-shaped deep-seated mass in the sacral foramina, showing branching pattern of growth associated with pressure bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the proposed method, the color histogram is extracted from the characteristic information of each moving object, and the histogram is continuously accumulated to avoid being sensitive to noise or changes, and the average value is obtained and stored. Finally, some comparison experiments prove the feasibility and applicability of the proposed algorithm [ 5 ]. Object detection and tracking are necessary and challenging activities in multiple PC vision scenarios such as security, motor vehicle navigation, and independent robot navigation.…”
Section: Introductionmentioning
confidence: 99%
“…In the proposed method, the color histogram is extracted from the characteristic information of each moving object, and the histogram is continuously accumulated to avoid being sensitive to noise or changes, and the average value is obtained and stored. Finally, some comparison experiments prove the feasibility and applicability of the proposed algorithm [ 5 ]. Object detection and tracking are necessary and challenging activities in multiple PC vision scenarios such as security, motor vehicle navigation, and independent robot navigation.…”
Section: Introductionmentioning
confidence: 99%
“…The only case was published by Sang Min Lee et al. [2] . They showed that a giant mass was detected in the foramen of the sacrum, accompanied by a branching pattern of growth and bone erosion of adjacent bones, but there was no significant bone destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Angioleiomyoma, a rare tumor consisting of mature smooth muscle cells and prominent vascular components, is classified by the World Health Organization (WHO) in 2013 as benign pericytic (perivascular) tumors [3] . It usually happens in the subcutaneous tissue of the limbs, presenting as painful, small, isolated solid mass [2] . Incidence peaks in people aged 40 to 60 years, mainly in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation